Organizing Networked Learning - Poorthuis, Anne-Marie (Proceedings of the International Conference on Networked Learning, 2012)
A networked context is dynamic. In this paper, I set up the organization of learning in a networked context starting from four leads. The first lead is analyzing involvement and acting as an example of a network. We view the network as a unit of analysis and the core of the network is the initiative. We make use of the involvement that the initiative radiates and attracts. I present the network analysis model as a means to order involvement and to identify different positions within a network. I also provide a vocabulary to communicate about them. The second lead is communicating knowledge and acting as an example of a node. We view the network as a knowledge infrastructure of nodes and links, that irrespective of size or capability provide access to knowledge in their own way. This is called a nodal network. The third lead is preparing effort and acting as an example of environment. We view the network as an inviting and challenging space in which various initiatives and networks come together, explore relationships, experiment, share and attune. An aid to creating an inviting environment is turning something into a theme. To create space we invite a diversity of related initiatives and networks to come together and learn from each other. The fourth and last lead is facilitating abilities and acting as an example of a programme. When we translate network into programme, we see a tissue of layers, lines, episodes and moments in which parties act, knowledge arises, effort emerges and the ability of the network to handle issues evolves into strategies, improvisations, habits and routines. Together, these leads offer a tangible steering framework for following and leading the otherwise so diffuse concept of ’network’. By unravelling ’network’ the way I propose here, we can find the leads to establish relationships, handle the dynamics and learn to organize in a networked context. This paper approaches learning in a networked context as a matter of organization and explores the leads that allow us to act in a networked context. After describing the four leads I present some cases and the issues they give rise to. These I consider my questions for further research. I conclude with some general remarks about the organization of networked learning.